2016
DOI: 10.1007/s12039-016-1079-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of citric acid on formation of oxides of Cu and Zn in modified sol-gel process: A comparative study

Abstract: We report here the influence of citric acid concentration on the formation of sol-gel products in each of Cu and Zn systems by using respective metal nitrate as precursor and citric acid as gelling agent. The synthesized sol-gel products were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive X-ray analysis (EDX), Fourier transform infra-red (FT-IR) spectroscopy and UV-Visible diffused reflectance spectroscopy (UV-Vis DRS). The influence of citric acid concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…However, a small increase of the crystallite size with the initial increment of CA/M is noticeable followed by a drop with a large excess of citric acid, becoming this tendency more evident when the samples are calcined at 1000 °C. Some authors reported the increment in crystallite size with the increase in citric acid, while others observed the opposite tendency , . The observations of these researchers, apparently contradictory, are in agreement with our results and could be explained due to the effect of the excess of citric acid on both gel self‐combustion temperature and time.…”
Section: Resultssupporting
confidence: 84%
“…However, a small increase of the crystallite size with the initial increment of CA/M is noticeable followed by a drop with a large excess of citric acid, becoming this tendency more evident when the samples are calcined at 1000 °C. Some authors reported the increment in crystallite size with the increase in citric acid, while others observed the opposite tendency , . The observations of these researchers, apparently contradictory, are in agreement with our results and could be explained due to the effect of the excess of citric acid on both gel self‐combustion temperature and time.…”
Section: Resultssupporting
confidence: 84%
“…The peaks present at 456, 712 and 1575 cm −1 represent the presence of Ni-O, C-C and C-H bonds, respectively. 25 According to the following carbothermal reaction, some Ni 2+ appeared to be reduced to elemental Ni in the presence of carbon: 27,28 2 1 2 peak that was observed at binding energy 872.5 eV. 29 The other peak seen at 854 eV in connection with a satellite peak of 860.9 eV, corresponds to the Ni p 2 3 2 spin-orbit levels of NiO.…”
Section: Resultsmentioning
confidence: 99%
“…A preliminary investigation of the sintering process was done in this work but no details on microstructral evolution or density were given. Many oxides like SrFeO2.85$_{\sim 2.85}$, CuO, ZnO, and so on have been made using a citric acid‐assisted modified Pechini method, 22,23 where the nitrates have been used as precursor and concentration of the citric acid varied 23 …”
Section: Introductionmentioning
confidence: 99%
“…21 A preliminary investigation of the sintering process was done in this work but no details on microstructral evolution or density were given. Many oxides like SrFeO ∼2.85 , CuO, ZnO, and so on have been made using a citric acid-assisted modified Pechini method, 22,23 where the nitrates have been used as precursor and concentration of the citric acid varied. 23 In the sol-gel method of combustion synthesis, the phase purity of the combustion product as well as the combustion behavior are predominantly determined by the stoichiometry (oxygen balance) between oxidizing and reducing agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation